2006
DOI: 10.1021/jf061260o
|View full text |Cite
|
Sign up to set email alerts
|

Critical Assessment of Various Techniques for the Extraction of Carotenoids and Co-enzyme Q10from the Thraustochytrid Strain ONC-T18

Abstract: A variety of techniques for extracting carotenoids from the marine Thraustochytrium sp. ONC-T18 was compared. Specifically, the organic solvents acetone, ethyl acetate, and petroleum ether were tested, along with direct and indirect ultrasonic assisted extraction (probe vs bath) methods. Techniques that used petroleum ether/acetone/water (15:75:10, v/v/v) with 3 h of agitation, or 5 min in an ultrasonic bath, produced the highest extraction yields of total carotenoids (29-30.5 microg g-1). Concentrations up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 21 publications
(34 reference statements)
0
18
0
1
Order By: Relevance
“…However, high temperature and oxygen may affect the stability of extracted carotenoids (Rodriguez-Amaya, 2001). Armenta et al (2006) reported that higher extraction yield of carotenoids from the marine fungi Thraustochytrium sp. ONC-T18 can be obtained by agitating the biomass in a solvent mixture of petroleum ether/acetone/water (15:75:10) for 3 h or sonication for five minutes.…”
Section: Discussionmentioning
confidence: 99%
“…However, high temperature and oxygen may affect the stability of extracted carotenoids (Rodriguez-Amaya, 2001). Armenta et al (2006) reported that higher extraction yield of carotenoids from the marine fungi Thraustochytrium sp. ONC-T18 can be obtained by agitating the biomass in a solvent mixture of petroleum ether/acetone/water (15:75:10) for 3 h or sonication for five minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Thraustochytrids can accumulate up to 80% of their dry cell weight as oil (Zuñiga, Ciobanu, Nuñeza, & Stark, 2012). Some researchers have explored thraustochytrids as producers for β-carotene and astaxanthin (Aki et al, 2003;Armenta, Burja, Radianingtyas, & Barrow, 2006;Quilodrán, Hinzpeter, Hormazabal, Quiroz, & Shene, 2010). Thraustochytrids are also reported to produce commercially important sterols such as squalene, cholesterol and stigmasterol .…”
Section: Introductionmentioning
confidence: 99%
“…Total carotenoids were expected to be fully extracted when the cell mass was suspended in acetone (Armenta et al, 2006), however after 3-4 extractions, the supernatant became colourless leaving behind a coloured biomass, which indicated complete extraction. When the cell suspension was subjected to ultrasonication for 30 min, a significant increase in carotenoid yield was observed (from 0.30 mg g -1 zeaxanthin and 0.10 mg g -1 β-carotene in direct extraction to 11.32 mg g -1 zeaxanthin and 5.07 mg g -1 β-carotene in ultrasonication) (Singh et al, 2013).…”
Section: Resultsmentioning
confidence: 99%